Zero-dimensional metal halide scintillator array and preparation method and application thereof

By combining the low-melting point zero-dimensional metal halide with wood naturally with a pore array structure, using negative pressure/normal pressure cycle operation and solvent and seed-assisted cooling and crystallization method, a composite scintillator with a nanowire array structure was prepared, which solved the problem that zero-dimensional metal halide scintillator in the prior art was difficult to form dense continuous nanowires, and efficient X-ray imaging was achieved.

CN119780998APending Publication Date: 2025-04-08NANJING UNIV OF POSTS & TELECOMM
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411995458.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In existing indirect X-ray detectors, zero-dimensional metal halide scintillators are difficult to form dense continuous nanowires, resulting in low load and light scattering problems, limiting their application in the field of X-ray imaging.

Method used

By combining the low melting point zero-dimensional metal halide with wood naturally having a pore array structure, using a negative pressure/normal pressure cycle operation and a method of solvent and seed-assisted cooling and crystallization, a composite scintillator with a nanowire array structure was prepared.

Benefits of technology

The orderly construction of the zero-dimensional metal halide scintillator array is achieved, which significantly improves its luminous efficiency and spatial resolution of X-ray imaging, and solves the problems of optical crosstalk and photon loss.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119780998A_ABST
    Figure CN119780998A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of indirect X-ray detectors, and particularly relates to a zero-dimensional metal halide scintillator array and a preparation method and application thereof. The scintillator array is obtained by melting a zero-dimensional metal halide, pouring the melted zero-dimensional metal halide into natural wood with a pore channel array structure and then performing crystallization; the specific preparation method comprises the steps that zero-dimensional metal halide is placed in a container to be heated and melted, and then natural wood is soaked in the zero-dimensional metal halide; then carrying out negative pressure treatment on the container, charging the container to normal pressure, and repeating negative pressure-normal pressure treatment for 2-4 times; and adding a solvent and a seed crystal into the container, cooling and recrystallizing to obtain the zero-dimensional metal halide scintillator array. According to the invention, a micron-sized pore channel array structure of natural wood is compounded with the zero-dimensional metal halide to construct a composite scintillator with optical waveguide characteristics, light is guided to be vertically propagated along the pore channel direction, optical crosstalk and photon loss are reduced, and the prepared scintillator array has good application prospects in X-ray imaging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of indirect X-ray detectors, and in particular relates to a zero-dimensional metal halide scintillator array and a preparation method and application thereof. Background Art

[0002] An indirect X-ray detector is a device that converts X-rays into visible light through a scintillator, and then converts the visible light into a digital signal for imaging. It has a wide range of applications in scientific research, medical imaging, security inspection, and industrial nondestructive testing. Currently, commercial scintillators are mainly inorganic scintillators, such as Bi4Ge3O 12 (BGO), Lu3A5O 12 :Ce 3+ (LuAG:Ce) and CsI:TI, etc. Although they have high light yield and strong attenuation ability for X-rays, they all have problems with preparation (such as complex production processes and capital-intensive equipment) and performance (such as mechanical flexibility and limited room for performance improvement); in recent years, zero-dimensional metal halides have become strong candidates for the next generation of scintillator materials due to their low-temperature solution preparation, excellent scintillation performance and highly tunable crystal structure. However, zero-dimensional metal halides mostly exist in the form of small-sized single crystals or polycrystalline powders. Among them, small-sized single crystals are difficult to meet the size required for actual imaging; and polycrystalline powders are mostly blended with polymers to make large-area thin films. Although X-ray imaging can be achieved, its light scattering phenomenon is serious, which limits its spatial resolution.

[0003] In view of this, people use vacuum-assisted methods to infuse metal halide precursor solutions into porous alumina (AAO) to prepare composite scintillators with nanowire array structures, thereby utilizing the difference in refractive index between the two to achieve longitudinal optical waveguides for scintillation light; however, AAO has the disadvantages of complex preparation process and high price, and its limited size makes it difficult to be applied in X-ray imaging. More importantly, in the above-mentioned solution-infusion-based method, the dissolution, solvent volatilization, crystal nucleation and growth processes of metal halides are difficult to balance, resulting in the difficulty of metal halides in AAO to form dense and continuous nanowires, and there are problems of low loading and light scattering due to the presence of holes.

[0004] Therefore, it has become a top priority to develop an efficient process method to achieve the orderly construction of zero-dimensional metal halide nanowire arrays based on a new matrix with a hole array structure. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention invents a composite preparation process based on low-melting-point zero-dimensional metal halides and natural wood with a pore array structure, thereby realizing the preparation of a zero-dimensional metal halide scintillator array and its application in the field of X-ray imaging.

[0006] In order to solve the above technical problems, the present invention discloses a zero-dimensional metal halide scintillator array, wherein the scintillator array is obtained by melting zero-dimensional metal halide and pouring it into natural wood with a channel array structure and then recrystallizing it.

[0007] Specifically, the zero-dimensional metal halide is A(DMSO) n [BCl m ], wherein A includes any one of Ga, Zr, and Y, and B includes any one of Sb, Bi, and Te;

[0008] Preferably, the zero-dimensional metal halide is Ga(DMSO)6SbCl6 or Zr(DMSO)8SbCl7;

[0009] Further preferably, the zero-dimensional metal halide is Ga(DMSO)6SbCl6.

[0010] The present invention also provides a method for preparing a zero-dimensional metal halide scintillator array, the specific steps of which are:

[0011] S1. Place zero-dimensional metal halide in a container, heat and melt it, and then immerse natural wood in it;

[0012] S2. The container is transferred to a vacuum heating device for negative pressure treatment;

[0013] S3. Fill the vacuum heating device to normal pressure, and repeat the negative pressure-normal pressure treatment 2 to 4 times;

[0014] S4. Adding a solvent and seed crystals into a container, cooling and recrystallizing to obtain a zero-dimensional metal halide scintillator array.

[0015] Specifically, the mass of the zero-dimensional metal halide is 1 to 5 g; preferably, the mass of the zero-dimensional metal halide is 1.5 to 3 g.

[0016] Specifically, the natural wood is cut perpendicular to the growth direction of the tree; the size of the natural wood is a×b×c, wherein 5mm≦a≦500mm, 5mm≦b≦500mm, 0.1mm≦c≦2.0mm;

[0017] Preferably, the natural wood is natural balsa wood, with a size of 15 mm×15 mm×1.2 mm;

[0018] Further preferably, the natural balsa wood is delignified balsa wood.

[0019] Specifically, in S1, the temperature of heating and melting is 60-150°C; preferably, the temperature of heating and melting is 90-110°C.

[0020] Specifically, in S2, the negative pressure treatment conditions are: vacuum degree of -1 to -90 kPa, time of 15 to 25 min, and temperature of 60 to 150° C.;

[0021] Preferably, the negative pressure treatment conditions are: vacuum degree of -60 to -80 kPa, time of 20 min, and temperature of 90 to 100°C.

[0022] Specifically, in S4, the solvent is dimethyl sulfoxide; the usage amount of the dimethyl sulfoxide is 0.05-0.2 ml; preferably, the usage amount of the dimethyl sulfoxide is 0.07-0.15 ml.

[0023] Specifically, in S4, the seed crystal has a particle size of 1 to 50 μm and an input amount of 2 to 20 mg;

[0024] Preferably, the seed crystal has a particle size of 20 to 50 μm and an input amount of 2 mg.

[0025] Specifically, in some embodiments of the present invention, by subjecting the prepared zero-dimensional metal halide scintillator array to ultraviolet light irradiation, fluorescence spectrum detection, spatial resolution detection and X-ray imaging detection, it is verified that the zero-dimensional metal halide scintillator array prepared by the present invention has good luminous efficiency and spatial resolution of X-ray imaging. The present invention utilizes the unique micron-scale hole array structure of delignified wood in the growth direction to compound it with a zero-dimensional metal halide with a large refractive index to construct a new composite scintillator with optical waveguide characteristics, thereby guiding light to propagate vertically along the hole direction, effectively reducing optical crosstalk and photon loss. Therefore, the zero-dimensional metal halide scintillator array has good spatial resolution in X-ray imaging, indicating that the zero-dimensional metal halide scintillator array has good application prospects in X-ray imaging.

[0026] Beneficial effects:

[0027] 1. Taking advantage of the melt-processable characteristics of low-melting-point zero-dimensional metal halides, the perfusion effect in the wood pores was enhanced through negative pressure / normal pressure cycle operation; on this basis, a method of solvent and seed crystallization assisted by cooling was innovatively proposed. The prepared zero-dimensional metal halide and wood composite scintillator showed significantly improved luminous efficiency compared with natural cooling;

[0028] 2. Taking advantage of the natural micron-hole array structure of wood and the difference in refractive index between wood and zero-dimensional metal halide (wood: 1.5; zero-dimensional metal halide: 1.8-2.5), the prepared composite scintillator has a pixelated array structure, which enables the scintillation light to be confined in the metal halide nanowires, effectively enhancing the longitudinal optical waveguide of the light field, thereby improving the spatial resolution of its X-ray imaging. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.

[0030] Figure 1 is the XRD pattern of Ga(DMSO)6SbCl6;

[0031] Figure 2 The in-situ cooling crystallization spectra of Ga(DMSO)6SbCl6, wherein (a) is the in-situ spectrum of Ga(DMSO)6SbCl6 natural cooling crystallization at room temperature, (b) is the in-situ spectrum of Ga(DMSO)6SbCl6 natural cooling crystallization at room temperature after adding DMSO and seed crystals, (c) (d) are the contour maps corresponding to (a) (b), respectively;

[0032] Figure 3 The photoluminescence quantum yield (PLQY) and spectrum of Ga(DMSO)6SbCl6 before and after cooling and crystallization, where (a) is the PLQY of Ga(DMSO)6SbCl6 before melting, (b) is the PLQY of molten Ga(DMSO)6SbCl6 after natural cooling and crystallization, (c) is the PLQY of molten Ga(DMSO)6SbCl6 after adding DMSO and seed crystals and cooling and crystallizing, (d) is the spectrum of the three crystals;

[0033] Figure 4 The following are photos of Ga(DMSO)6SbCl6@WOOD, where (a) is taken under natural light and (b) is taken under UV light.

[0034] Figure 5 The cross-sectional SEM images of delignified balsa wood and Ga(DMSO)6SbCl6@WOOD;

[0035] Figure 6 The excitation and emission spectra of Ga(DMSO)6SbCl6@WOOD;

[0036] Figure 7 The spatial resolution and X-ray imaging photos of Ga(DMSO)6SbCl6@WOOD, where (a) is the line pair card imaging, (b) is the spatial resolution, (c) is the actual image of the earphone, and (d) is the X-ray imaging;

[0037] Figure 8 is the spatial resolution of Ga(DMSO)6SbCl6@WOOD#Low, where (a) is the line pair card imaging image and (b) is the spatial resolution;

[0038] Fig. 9is the spatial resolution of Zr(DMSO)8SbCl7@WOOD, where (a) is the line pair card imaging and (b) is the spatial resolution. DETAILED DESCRIPTION

[0039] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.

[0040] The specific preparation method of delignified balsa wood used in the following examples is as follows: 1.3 mm thick natural balsa wood chips were brushed with sodium hydroxide (10 wt%) and hydrogen peroxide (30 wt%) respectively, and then irradiated with 365 nm-ultraviolet light until the wood completely turned white, and the color change from brown to white was due to the removal of chromophores in lignin. Then, the treated wood chips were soaked in ethanol for 5 hours to remove the remaining chemicals, and then vacuum dried to obtain delignified balsa wood.

[0041] Example 1: Preparation of Ga(DMSO)6SbCl6

[0042] A method for preparing zero-dimensional metal halide Ga(DMSO)6SbCl6, the specific steps are as follows:

[0043] (1) Add 176.0 mg GaCl3 and 228.1 mg SbCl3 to 2 mL DMSO;

[0044] (2) then stirred and heated at 70°C to obtain a colorless solution;

[0045] (3) The solution was cooled to room temperature at a rate of 5°C / h and then stored at room temperature for 12 h, thereby forming [Ga(DMSO)6][SbCl6] crystals.

[0046] X-ray diffractometer (XRD) was used to characterize Ga(DMSO)6SbCl6. The specific steps were as follows: Ga(DMSO)6SbCl6 crystals were placed in the sample slot of an X-ray diffractometer (D8 Advance, Bruker) and scanned. Figure 1 is the XRD spectrum of Ga(DMSO)6SbCl6. It can be seen from the figure that the diffraction peak of the sample corresponds to the diffraction peak of Ga(DMSO)6SbCl6 obtained by calculation;

[0047] The in-situ spectrometer was used to characterize the Ga(DMSO)6SbCl6 spectrum. The specific steps were as follows: 1.5g of Ga(DMSO)6SbCl6 crystals were placed in a culture dish and heated at 90°C for 20 minutes under vacuum to melt; the culture dish was transferred to room temperature for natural cooling and crystallization, and a 365nm laser was used as excitation, and a NOVA cryo-spectrometer (Idea Optics) was used to collect the in-situ spectrum of Ga(DMSO)6SbCl6. The in-situ cooling crystallization spectrum of Ga(DMSO)6SbCl6 in this example is shown in Figure 2 , (a) is the in-situ spectrum of the natural cooling crystallization of liquid Ga(DMSO)6SbCl6 at room temperature. It can be seen that the spectrum of the final natural crystallization is red-shifted compared with the original Ga(DMSO)6SbCl6, and its photon luminescence quantum efficiency is also reduced ( Figure 3 ), which may be caused by the loss of DMSO during vacuum heating, so the present invention intends to use supplementation of DMSO and introduction of seed crystals to induce crystallization. (b) is an in-situ spectrum of natural cooling crystallization at room temperature after supplementation of DMSO and seed crystals. It can be seen that the crystallization quality and efficiency are greatly improved after supplementation of DMSO and introduction of seed crystals; (c) (d) are contour maps corresponding to (a) (b).

[0048] The photoluminescence quantum efficiency was measured using a spectrophotometer equipped with an integrating sphere (FLS980, Edinburgh). The photoluminescence quantum yield (PLQY) of Ga(DMSO)6SbCl6 before and after cooling and crystallization in this example is shown in the spectrum. Figure 3 , (a) is the PLQY of Ga(DMSO)6SbCl6 before melting, (b) is the PLQY of molten Ga(DMSO)6SbCl6 after natural cooling and crystallization, (c) is the PLQY of molten Ga(DMSO)6SbCl6 after solvent supplementation and seed crystallization, and (d) is the spectrum of the three crystals. It can be seen that under the influence of solvent supplementation and seed crystal induction, its PLQY increases significantly, and its crystallization quality and efficiency are greatly improved.

[0049] Example 2: Preparation of Ga(DMSO)6SbCl6@WOOD

[0050] A preparation method of a zero-dimensional metal halide array scintillator Ga(DMSO)6SbCl6@WOOD, the specific steps are as follows:

[0051] (1) 1.5 g of Ga(DMSO)6SbCl6 crystals prepared in Example 1 were placed in a petri dish and heated to 90° C. to melt, and then a 15 mm×15 mm×1.2 mm delignified balsa wood was immersed in the molten Ga(DMSO)6SbCl6;

[0052] (2) Transferring the culture dish to a vacuum heating device for negative pressure treatment, the vacuum degree of the negative pressure treatment is -60 to -80 kPa, the time is about 20 minutes, and the temperature is 90 to 100°C;

[0053] (3) Filling the vacuum heating device to normal pressure;

[0054] (4) Repeat the above steps (2) and (3) three times;

[0055] (5) Add 0.07 ml DMSO and 2 mg Ga(DMSO)6SbCl6 seed crystals (particle size of 20-50 μm) into a culture dish and cool naturally at room temperature to crystallize to obtain Ga(DMSO)6SbCl6@WOOD.

[0056] The zero-dimensional metal halide array scintillator Ga(DMSO)6SbCl6@WOOD prepared in Example 2 was characterized.

[0057] Figure 4 The following are the photos of Ga(DMSO)6SbCl6@WOOD, where (a) is taken under natural light and (b) is taken under ultraviolet light. Figure 4 It can be seen that after Ga(DMSO)6SbCl6 is fully compounded with delignified wood, Ga(DMSO)6SbCl6@WOOD can produce bright cyan light under the irradiation of ultraviolet light;

[0058] The cross sections of delignified balsa wood and Ga(DMSO)6SbCl6@WOOD were characterized by scanning electron microscopy (SEM, Hitachi S4800). Figure 5 (a) is a cross-sectional scanning electron microscope image of delignified balsa wood before melt infusion. It can be seen from the figure that the delignified balsa wood has natural micron-scale channels (such as the red frame area). (b) is a cross-sectional scanning electron microscope image of Ga(DMSO)6SbCl6@WOOD. It can be seen from the figure that Ga(DMSO)6SbCl6 fully enters the micron-nanoscale channel array of delignified balsa wood and then crystallizes after cooling.

[0059] The excitation and emission spectra of Ga(DMSO)6SbCl6 were tested using a fluorescence spectrophotometer (F-4700, HITACHI). Figure 6 It is the excitation and emission spectrum. It can be seen from the figure that the optimal excitation and emission are 352nm and 515nm respectively. The sample exhibits bright cyan photoluminescence under ultraviolet irradiation.

[0060] The imaging spatial resolution and X-ray imaging photos of the zero-dimensional metal halide array scintillator array Ga(DMSO)6SbCl6@WOOD in this embodiment are shown in Figure 7, where the X-ray images of different objects were obtained on a homemade device consisting of an AMPTEK mini x2 X-ray tube, a prism, and a digital camera (D850, Nikon). The target object was placed on top of the scintillator film, and the X-ray tube was placed above the target object with an object-source distance of 1 cm. The modulation transfer function (MTF) was measured using the slanted edge method, specifically, a 1 mm thick tungsten sheet with a sharp edge was placed on the scintillator film, and then the X-ray images of the slanted edge were recorded. Based on the slanted edge profile of the image, the edge spread function (ESF) was derived in Matlab, and then the ESF was differentiated to obtain the LSF, and the MTF was obtained by Fourier transform; Figure 7 (a) is the line pair card imaging, (b) is the spatial resolution, (c) and (d) are the actual image and X-ray imaging of the headset. Figure 7 It can be seen that X-ray imaging can achieve good spatial resolution and can provide very clear detection imaging of the interior of the headphones.

[0061] Example 3: Preparation of Ga(DMSO)6SbCl6@WOOD#Low

[0062] The difference between this embodiment and embodiment 2 is that DMSO is not supplemented and seed crystals are not introduced during the cooling crystallization process in step (5), and the rest of the preparation method is the same as that in embodiment 2, to prepare Ga(DMSO)6SbCl6@WOOD#Low.

[0063] The imaging spatial resolution of Ga(DMSO)6SbCl6@WOOD#Low was tested using the same method as in Example 2. Figure 8 As a specific result of the imaging spatial resolution, it can be seen that in the absence of solvent supplementation and seed induction, the resolution of Ga(DMSO)6SbCl6@WOOD#Low (3.2lp / mm) is greatly reduced compared to the resolution of Ga(DMSO)6SbCl6@WOOD in Example 2 (6.2lp / mm).

[0064] Example 4: Preparation of Zr(DMSO)8SbCl7@WOOD

[0065] The Ga(DMSO)6SbCl6 crystal in step 1 is replaced with Zr(DMSO)8SbCl7, wherein the synthesis steps of Zr(DMSO)8SbCl7 are as follows:

[0066] (1) Add 233.0 mg ZrCl4 and 228.1 mg SbCl3 to 2 mL DMSO;

[0067] (2) then stirred and heated at 70°C to obtain a colorless solution;

[0068] (3) The solution was cooled to room temperature at a rate of 5°C / h and then stored at room temperature for 12 h, thereby forming Zr(DMSO)8SbCl7 crystals.

[0069] The remaining preparation methods are the same as those in Example 2 to obtain the zero-dimensional metal halide array scintillator Zr(DMSO)8SbCl7@WOOD of this embodiment. The imaging spatial resolution and X-ray imaging photos thereof are shown in FIG. Fig. 9 , where (a) is the line pair card imaging diagram and (b) is the spatial resolution. It can be seen that its performance is poorer than that of Ga(DMSO)6SbCl6@WOOD, but still higher than that of Ga(DMSO)6SbCl6@WOOD#Low.

[0070] The present invention provides a zero-dimensional metal halide scintillator array and a method for preparing and applying the same. There are many methods and approaches to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention. All components not specified in this embodiment can be implemented by existing technologies.

Claims

1. A zero-dimensional metal halide scintillator array, characterized in that: The scintillator array is obtained by melting zero-dimensional metal halide and pouring it into natural wood with a channel array structure, followed by recrystallization.

2. The scintillator array according to claim 1, characterized in that: The zero-dimensional metal halide is A(DMSO) n [BCl m ], wherein A includes any one of Ga, Zr, and Y, and B includes any one of Sb, Bi, and Te.

3. A method for preparing a zero-dimensional metal halide scintillator array, characterized in that: The specific steps are: S1. Place zero-dimensional metal halide in a container, heat and melt it, and then immerse natural wood in it; S2. The container is transferred to a vacuum heating device for negative pressure treatment; S3. Fill the vacuum heating device to normal pressure, and repeat the negative pressure-normal pressure treatment 2 to 4 times; S4. Adding a solvent and seed crystals into a container, cooling and recrystallizing to obtain a zero-dimensional metal halide scintillator array.

4. The preparation method according to claim 3, characterized in that: The mass of the zero-dimensional metal halide is 1 to 5 g.

5. The preparation method according to claim 3, characterized in that: The natural wood is cut perpendicular to the growth direction of the tree; the size of the natural wood is a×b×c, wherein 5mm≦a≦500mm, 5mm≦b≦500mm, and 0.1mm≦c≦2.0mm.

6. The preparation method according to claim 3, characterized in that: In S1, the heating and melting temperature is 60 to 150°C.

7. The preparation method according to claim 3, characterized in that: In S2, the negative pressure treatment conditions are: vacuum degree of -1 to -90 kPa, time of 15 to 25 min, and temperature of 60 to 150°C.

8. The preparation method according to claim 3, characterized in that: In S4, the solvent is dimethyl sulfoxide; the usage amount of the dimethyl sulfoxide is 0.05-0.2 ml.

9. The preparation method according to claim 3, characterized in that: In S4, the seed crystal has a particle size of 1 to 50 μm and an input amount of 2 to 20 mg.

10. Use of the zero-dimensional metal halide scintillator array according to claim 1 or 2 in X-ray imaging.